Community projects as social activism from direct action to direct services - Shepard, Benjamin 1969- (Thousand Oaks, CA SAGE Publications, Inc., 2015)
"Community projects as social activism: from direct action to direct services by Benjamin Shepard is an engaging and accessible work that will get today's student's excited about the very real prospect of achieving lasting, positive change within their communities. The book outlines a distinct approach to community practice born out of the intersection of social movements, day-to-day organizing, and the lessons from five decades of community change practices. This invaluable resource is a must-have for anyone involved in community organization, community health, and community activism practice research and policy"--Page 4 of cover.
Foreword -- Author -- Acknowledgments -- About the author -- Theory, contexts and understandings -- On community practice -- Activism in a changing world : looking back to move forward -- Learning from community projects -- In conclusion -- Practice and power -- Social action and reclaiming power -- Identifying issues and goal-setting -- Research as action -- Mobilization and spreading the message -- Direct action and ?getting the goods? -- Legal strategies, social services, and social movements -- Praxis: from direct action to direct services -- Social movement to social services: from the black panthers to the young lords -- From critique to coexistence with capital: the woodlawn organization and the -- Act up to the world: direct action to direct services -- Harm reduction and human services: experiments in syringe exchange -- The perils of the nonprofit industrial complex -- Diy politics and world-making: mutual aid, anarchism, and alternative solutions -- Multi-issue organizing: from the women's movement to struggles for global -- Community building against inequality: zapatistas, occupations, and transnational advocacy -- References -- Index.
Includes bibliographical references (pages 207-225) and index.
Keywords: Social movements -- United States; Community-based social services -- United States; Political participation -- United States